Self‐Care. Issue 2 (3rd May 2022) - Rosenbaum, Susanna; Talmor, Ruti
Abstract: Self‐care is everywhere these days. Unlike "care, " it is not yet a central term in anthropology, but recent ethnographic studies point up its potential. In this keyword entry, we trace out distinct yet co‐present understandings of the term that stem from radically different worldviews and construct it in oppositional, mutually exclusive ways. The first is the Black feminist lineage, which defines self‐care as a political warfare within and against an American system of intersectional oppression. The second is a multidisciplinary body of work which builds on Foucault and defines self‐care as a neoliberal form of domination and subjectification. Finally, we examine a burgeoning literature on refusal that emerges from multiple disciplines, including queer and affect theory, Native studies, Black feminism, and disability studies. Centering the margins, this perspective directly speaks to processes of domination, elucidating the recursive relationship among self, care, and personhood—how practices of care produce persons, and in turn, how only those accorded full personhood are deemed worthy of care. Containing these multiple and conflicting definitions, self‐care thus exposes the current experience of crisis as bifurcated: either hopelessly ongoing or hopefully at a breaking point that will lead to change.